DAMPAK PENERAPAN TEKNOLOGI INFORMASI ELECTRONIC DATA INTERCHANE TERHADAP KINERJA PERUSAHAAN FORWARDING - Agus Agus Sunaryo (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2009)
Electronic Data Interchane (EDI) is combination of computer technologogy and electronic which com help us to communication and serving document trafficbetween two side or more with the same time in fast and accurate. Mi – Trans Logistic corporation who starting to use EDI in its business operation, received a lot gains, Al thought in start its needed great investment and the up grade of the human resources. The gains are: repare the data lack; less paper and loose the face to face amount with customer because the document manufactured by the electronic so that be data will received efficiency and time efectivy, increase serving to consument beside that. The EDI impact are the custom document serving is easier and faste,. where before EDI it need stime 4 – 5 days, now can served only less 3 days, and the important thing is the image from the customer if the company are developed and bonafide and prestice.